Repair-oriented design and manufacturing strategies for circular electronic products, from mass customization/standardization to scalable repair economy - Bahram Ipaki; Zohrehsadat Hosseini (Results in Engineering)
Repair-oriented design (RoD) seeks to enhance repairability and repair value within a circular economy by focusing on extended repair loops that account for repeated repairs, diagnostics, facilities, speed, accuracy, safety, user preferences, skills, demand scale, and post-sale service. However, challenges such as producers’ profit complexities, geographical variability, and repair costs hinder repair activities, especially in the electronics sector. We propose innovative RoD strategies that are integrated by mass customization (MC) and mass standardization (MS) with the aim of align manufacturers’ business interests with sustainability goals, adapting to diverse global standards, and enhancing user engagement in repairs. Utilizing a mixed-method approach including a systematic review, technician surveys, and quantitative and qualitative analyses via AHP and QFD, this research identifies key parameters for RoD and develops five integrated strategies: self-repairing through MC, co-repairing through MC, advanced-repairing through MS, middle-scale repairing through MC, and large-scale repairing through MS.This study also identified 28 barriers and 56 drivers affecting RoD implementation, providing a framework for optimizing circular design and production processes. Alternatively, our study reflected several key findings engaged with industry and policies. Achieving repairability and maintenance efficiency requires balancing design simplicity with functionality. While modular designs facilitate easy part replacement, they can complicate assembly if standards are inconsistent. Effective diagnostic features and accessible technical information improve problem-solving. Fast disassembly is supported by magnetic or temporary connections and durable materials and preventive maintenance programs can extend part lifecycles. Accessible arrangements like color-coded parts, clear labeling and technician training boost efficiency and reliability during repairs.